PWE-054 Independent validation of the ibd-control questionnaire: results from a large-scale electronic patient experience survey (ibd2020). (22nd June 2015) - Bodger, K; Gledhill, T; Driscoll, R; Terry, H; Irving, P; Travis, S
Abstract : Introduction: The IBD-Control Questionnaire is a self-completed patient reported outcome measure developed to rapidly capture disease control from the patient perspective. 1 Eight of the question items generate a summary score (IBD-Control-8) ranging from 0 (worst control) to 16 (best control). We aimed to evaluate the feasibility of capturing the items electronically (rather than on paper) and to validate their measurement properties independently within the setting of a large-scale UK patient experience survey. Method: The IBD2020 survey was an electronic (online) questionnaire of patient experiences of healthcare across Europe, promoted in the UK by the national charity, Crohn's and Colitis UK. The survey included items about sociodemographics, disease type, treatments, self-reported disease activity (last 3 months), relapse status (last 12 months), disease impact and a wide range of questions about care experiences. The IBD-Control-8 questions were incorporated into the UK survey, allowing an opportunity to validate its performance. Results: 818 UK patients completed the survey (Female n = 611; Under 30 years, n = 259; 30–44 yrs n = 352; 45–59 yrs 1n=42, 60 yrs plus n = 45; CD n = 483; Previous surgery n = 275; Current stoma n = 69). Self-reported disease activity in last 3 months: Remission 10.8%, Minimal 21.1%, Mildly 28.0%, Moderately 22.1%, Severely 8.7%, Missing 9.3%. 701/818 (85.7%) completed all IBD-Control-8 questions, (mean score [sd]: 7.3 [4.9]; range: 0–16). Internal consistency was strong (Cronbach's alpha: 0.82). Construct validity of IBD-Control-8 was confirmed by: (a) moderately strong negative correlation (Spearman's rho values) with 'Disease Activity In Last 3 months' (Overall -0.68; CD -0.67; UC -0.66; Post-surgery -0.65) and 'Number of Relapses in Last 12 months' (Overall -0.61; CD -0.59; UC -0.60; Post-surgery -0.58) and (b) Significantly higher mean [sd] scores for remission versus any level of disease activity (13.1 [3.1] versus 6.4 [4.5]; p < 0.001). Utility of IBD-Control-8 as a screening test to identify 'quiescent' patients (score of 13+) was confirmed (specificity: 88.2% versus self-reported 'remission' status; 95% versus remission or minimal activity). Conclusion: The IBD-Control-8 items from the IBD-Control Questionnaire are well suited to large-scale electronic surveys, with excellent completion rates within a lengthy patient experience survey. This study provides independent confirmation of its previously reported psychometric properties in a large cohort of UK patients. Disclosure of interest: None Declared. Reference: Bodger, et al . Gut. 2014;63(7):1092–102